The role of vocabulary breadth and depth in predicting second language descriptive writing performance. Issue 5 (20th October 2019) - Dabbagh, Ali; Janebi Enayat, Mostafa
ABSTRACT: The present study investigates the interaction between vocabulary breadth and depth on the one hand and assessments of L2 learners' descriptive writing on the other. The predictive role of these two dimensions of vocabulary knowledge in relation to the vocabulary component of the assessment was also examined. The extent to which vocabulary knowledge at various word-frequency levels predicted overall descriptive writing performance as well as scores on the vocabulary component was investigated. For this purpose, 67 English as a Foreign Language students took the Vocabulary Levels Test, Word Associates Test, and undertook two descriptive writing tasks. Results of correlations and stepwise regressions indicated that (a) vocabulary breadth was predictive of overall assessment of descriptive writing while vocabulary depth only correlated with the overall assessment; (b) vocabulary breadth was also predictive of the vocabulary component of L2 descriptive writing, but vocabulary depth was again simply correlated with this variable and (c) while mid-frequency vocabulary was correlated with, and predictive of, the overall assessment of descriptive writing, knowledge of low-frequency words was a strong factor in explaining the variance in the vocabulary component. The results are explained with reference to the emphasis on lexical diversity and sophistication in the vocabulary assessment criteria.